2004
DOI: 10.1097/01.sla.0000114217.52941.c5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Botulinum Toxin Versus Laparoscopic Heller Myotomy for Esophageal Achalasia

Abstract: Laparoscopic myotomy is as safe as BoTx treatment and is a 1-shot treatment that cures achalasia in most patients. BoTx should be reserved for patients who are unfit for surgery or as a bridge to more effective therapies, such as surgery or endoscopic dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(123 citation statements)
references
References 22 publications
4
112
0
7
Order By: Relevance
“…A randomized controlled trial published in 2017 comparing POEM with pneumatic dilation found the POEM procedure to be more efficacious in terms of therapeutic success, but also more likely to result in post-procedure reflux oesophagitis 61 . The preceding discussion makes no mention of medical treatments for achalasia, specifically botulinum toxin [62][63][64][65] , calcium-channel blockers 66 , nitrates 66 and phosphodiesterase type 5 inhibitors 67 primarily because, although these agents provide some symptomatic benefit, they are not durable therapies and they do not halt the disease progression toward oesophageal decompensation characterized by dilatation and food retention. For example, in the case of botulinum toxin injected into the LES, about two-thirds of patients with achalasia report an improvement in dysphagia, but most relapse within a year and repeat treatments have diminished effectiveness, making it a poor firstline therapy [62][63][64][65] .…”
Section: Poemmentioning
confidence: 99%
“…A randomized controlled trial published in 2017 comparing POEM with pneumatic dilation found the POEM procedure to be more efficacious in terms of therapeutic success, but also more likely to result in post-procedure reflux oesophagitis 61 . The preceding discussion makes no mention of medical treatments for achalasia, specifically botulinum toxin [62][63][64][65] , calcium-channel blockers 66 , nitrates 66 and phosphodiesterase type 5 inhibitors 67 primarily because, although these agents provide some symptomatic benefit, they are not durable therapies and they do not halt the disease progression toward oesophageal decompensation characterized by dilatation and food retention. For example, in the case of botulinum toxin injected into the LES, about two-thirds of patients with achalasia report an improvement in dysphagia, but most relapse within a year and repeat treatments have diminished effectiveness, making it a poor firstline therapy [62][63][64][65] .…”
Section: Poemmentioning
confidence: 99%
“…31 The clinical effects of a single injection are short lived with relapse in more than 50% within 6 months. 28 However, repeated injections may confer clinical benefit in 70% to 90%. 32 In one report, 21% of newly diagnosed achalasia patients were treated with BTox as the initial modality of treatment with an average duration of effect of 6 months.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…34 Usually, 80 to 100 units of BTox-A are injected in each quadrant of the LES in 0.5 to 1ml aliquots. 28 This improves the symptoms of achalasia, decrease LES pressure, increase lower esophageal aperture and improve esophageal emptying. 31 The clinical effects of a single injection are short lived with relapse in more than 50% within 6 months.…”
Section: Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the action only persist for 3 to 4 months, half of patients relapse and need reintervention at 6-24 months after the first injection, thus limiting the use in clinical practice. There is some evidence that repeated injections could affect the subsequent surgical miotomy, thus the use of Botox should be reserved to elderly patients or patients with associated pathology who have contraindications for endoscopic dilation or miotomy (28)(29)(30).…”
Section: Endoscopic Injection Of Botoxmentioning
confidence: 99%